The Influence of Sharia Financial Literacy, E-Commerce, Payment Gateway, and Media Social on The Performance Of UMKM (Coffee Shops) In Medan City - Amelia, Cahya; Nurbaiti, Nurbaiti; Qarni, Waizul (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Purpose: This research aims to examine the influence of Sharia financial literacy, e-commerce, payment gateways, and Media Social on the performance of UMKM (coffee shops) in Medan City. Design/Method/Approach: The research method uses a quantitative approach with multiple linear regression analysis techniques and is processed using SPSS. The research sample consists of 105 respondents, selected based on predetermined criteria: UMKM coffee shop entrepreneurs. Findings: Sharia Financial Literacy has a significant influence because it helps MSME actors manage their finances more wisely and use Sharia principles, thereby increasing efficiency and consumer trust. Payment Gateway also has a considerable impact as it facilitates fast and secure digital transactions, which are essential in today’s cashless society. Social Media is likewise substantial because it is a low-cost promotional tool with a broad reach, enabling MSMEs to build social relationships and a strong brand image. E-commerce does not significantly influence, possibly because not all MSME coffee shops in Medan have fully optimized e-commerce platforms due to limitations in technology, knowledge, or consumer preferences that still lean toward offline transactions. Originality/Values: The originality of this study lies in its integrated analysis of Sharia financial literacy, e-commerce, payment gateways, and social media in the specific context of coffee shop MSMEs in Medan City, offering a holistic view rarely explored in previous research. The findings can be implemented by promoting Sharia-based financial education, encouraging digital payment systems, and providing social media marketing training. Given the low impact of e-commerce, targeted digital transformation programs are needed to overcome local technological and knowledge barriers. These steps can help stakeholders support the sustainable growth of MSMEs in urban Muslim communities.